Social dimensions of recycling of photovoltaics panels – conceptual framework based on literature review - Chrzanowski, Maciej; Zawada, Piotr (Journal of Modern Science, 2025)
Objectives There is a need to create a conceptual framework at the level of social dimensions of recycling photovoltaic panels, due to the fact that this aspect has so far been analysed primarily in terms of economic and ecological aspect. Material and methods To fill this gap, the method of systematic literature review was chosen, the aim of which was to create a conceptual framework and identify key social factors influencing the behaviour related to the recycling of photovoltaic panels, both by households and industrial in-stallations and solar farms. Results Analysing and using the social structure of a given region/country in order to op-timize activities at the level of increasing social awareness in the context of recycling photovoltaic panels. Conclusions Development of regional and national policies that promote recycling attitudes at the level of photovoltaic panels, taking into account economic, ecological and social in-centives. Development of infrastructure for the efficient process of recycling photovoltaic panels by individual consumers, due to the fact that the recycling process of photovoltaic panels in the case of industrial installations is much more developed, structured and logistically optimized.